Inventory Assessment Innovation in Teaching Speaking Skills Islamic Junior High School - Yusril Muhammad Nur; R. Umi Baroroh; Islam Youssry Elhadky (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to innovate inventory assessment and carry out updates in inventory assessment instruments. This research used a